ANALISIS KUALITAS PRODUK MINUMAN KEKINIAN BERDASARKAN PREFERENSI KONSUMEN DI KOTA BATAM - Ardian, Jhony; Fajrah, Nofriani (Computer Science and Industrial Engineering, 2023)
The popularity of contemporary drinks is currently increasing to build a new business model and even develop. Today's most popular drinks are the most popular. The problem that occurs is the seller who participates in making a business selling contemporary drinks but ignores the critical quality that must be met in contemporary drinks based on consumer preferences in Batam City. The purpose of this study is to compile critical quality criteria for contemporary beverage products based on consumer preferences in Batam City. The approach used in this study is Quality Function Deployment (QFD) displayed in the House of Quality (HOQ). Based on research that has been done it can be concluded that the criteria for critical quality in contemporary beverage products based on consumer preferences in Batam City are taste, price level, ease of getting products, brand logos, size/volume packaging, composition safety, presentation method, health service permit, The existence of a halal label, has a scent, and there is information on the nutritional value on packaging successively considered important by contemporary drink consumers in Batam City.